2013
DOI: 10.1190/geo2012-0074.1
|View full text |Cite
|
Sign up to set email alerts
|

A fast interpretation of self-potential data using the depth from extreme points method

Abstract: We used a fast method to interpret self-potential data: the depth from extreme points (DEXP) method. This is an imaging method transforming self-potential data, or their derivatives, into a quantity proportional to the source distribution. It is based on upward continuing of the field to a number of altitudes and then multiplying the continued data with a scaling law of those altitudes. The scaling law is in the form of a power law of the altitudes, with an exponent equal to half of the structural index, a sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The SP anomaly (V ) due to a semi-infinite vertical cylinder, infinitely long horizontal cylinder, or sphere ( Figure 1) at a point P (x) along a profile has a closed-form solution, and is given by Abdelrahman et al, 2004;El-Araby, 2004;Essa et al, 2008;Monteiro Santos, 2010;Fedi and Abbas, 2013)…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The SP anomaly (V ) due to a semi-infinite vertical cylinder, infinitely long horizontal cylinder, or sphere ( Figure 1) at a point P (x) along a profile has a closed-form solution, and is given by Abdelrahman et al, 2004;El-Araby, 2004;Essa et al, 2008;Monteiro Santos, 2010;Fedi and Abbas, 2013)…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Gokturkler and Balkaya (2012) described three global optimization approaches based on stochastic algorithms (genetic algorithm (GA), simulated annealing (SA), and particle swarm optimization (PSO)) to invert SP anomalies by some polarized bodies of simple geometries, and concluded that the inverse parameters recovered by the GA, SA and PSO are in good agreement. Fedi and Abbas (2013) developed a fast imaging technique (the so called depth from extreme points (DEXP) method) based on the upward continuation to interpret SP anomalies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…To circumvent this effect, we present a new multiscale method, which is highly stable vs. high wavenumber noise. In particular, we will consider the DEXP transformation (Fedi, 2007;Fedi and Abbas, 2013) of the LWN and will derive a simple scaling-law, which is specific for this function.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these methods have been improved in order to be applied in gradient tensor data interpretation, such as the migration method (Zhdanov et al 2011(Zhdanov et al , 2012 and the correlation (probability) method (Guo et al 2009). Fedi and Abbas (2013) demonstrated that it also is a reliable method to interpret self-potential data. It has shown many advantages over other methods due to its flexible form of depth weighting.…”
Section: Introductionmentioning
confidence: 99%